2021
DOI: 10.3390/gels7030101
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible and Enzymatically Degradable Gels for 3D Cellular Encapsulation under Extreme Compressive Strain

Abstract: Cell encapsulating scaffolds are necessary for the study of cellular mechanosensing of cultured cells. However, conventional scaffolds used for loading cells in bulk generally fail at low compressive strain, while hydrogels designed for high toughness and strain resistance are generally unsuitable for cell encapsulation. Here we describe an alginate/gelatin methacryloyl interpenetrating network with multiple crosslinking modes that is robust to compressive strains greater than 70%, highly biocompatible, enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In addition, sodium citrate is also a good chelating agent and has good complexing ability for metal ions, such as Ca 2+ and Mg 2+ in water. Alginate is a kind of natural polymer, which is often used in the treatment of heavy metal poisoning and as a drug sustained-release agent [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sodium citrate is also a good chelating agent and has good complexing ability for metal ions, such as Ca 2+ and Mg 2+ in water. Alginate is a kind of natural polymer, which is often used in the treatment of heavy metal poisoning and as a drug sustained-release agent [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the elasticity and toughness of the prepared materials could be controlled either by incorporation of PU within the Xn matrix, or by its modification with OA. Other authors reported similar results related to the same systems loaded with antifungal or anti-inflammatory compounds [ 15 ], or for other gels based on an alginate/gelatin methacryloyl interpenetrating network [ 34 ] nano clay and natural polysaccharides [ 35 ], or for sponge-based systems on two oppositely charged polyelectrolytes (chitosan and poly(cyclodextrin citrate)) [ 36 ].…”
Section: Resultsmentioning
confidence: 62%
“…For tissue engineering, well-tuned scaffold mechanics are a crucial property. One advantage of alginate hydrogels is their ability to take on finely tuned mechanical properties. , Future work in optimizing CC crosslinked alginate hydrogel mechanics may also prove instrumental in applying this technology to tissue engineering challenges.…”
Section: Implications For Biomaterials Design and Future Directionsmentioning
confidence: 99%
“…Hydrogels based on diverse natural and synthetic polymers have been used as scaffolds for tissue engineering. Alginate hydrogels in particular are notable for their biocompatibility with somatic and multipotent cells, robust mechanical properties, mild conditions of gelation, ease of modification, and structural similarities to extracellular matrix, which has made alginate a widely used and effective scaffold material. , Although alginate is easy to crosslink non-covalently with the addition of Ca 2+ ions, Ca 2+ -alginate gels have been shown in vivo to leach Ca 2+ into the physiological environment through cation exchange. , In particular, this presents difficulties because extracellular Ca 2+ is known to stimulate activation of the NLRP3 inflammasome pathway via stimulation of G protein-coupled calcium sensing receptors . Although Ca 2+ crosslinked alginate hydrogels have remained effective and viable scaffolds for many tissue engineering applications, concerns over this pro-inflammatory effect, which has been observed both in vitro and in vivo leading to elevated expression of IL-1β, have led to an interest in Ca 2+ -free methods of crosslinking alginate .…”
Section: Introductionmentioning
confidence: 99%